UI/UX Design of Influencer Selection Application with User Centered Design Method - Choki Ferdiyansyah; Arif Amrulloh; Maryona Septiara (Postgraduate, University of Mataram, 2025)
The manual influencer selection process at PT Karya Dari Desa is inefficient and prone to subjective decision-making due to the lack of standardized criteria. This study aims to design a UI/UX prototype for an influencer selection application using the User-Centered Design (UCD) method to improve efficiency and objectivity. The UCD process included understanding the context of use, identifying user requirements, designing solutions, and evaluating the prototype. Early-stage analysis revealed the need for structured influencer data, filtering based on measurable performance metrics, comparative evaluation, and objective ranking. The developed prototype enables users to filter and compare influencers and automatically generate rankings using the Auto WASPAS method. Evaluation was conducted with 12 users through task-based testing and the User Experience Questionnaire (UEQ). The results show a task success rate of 96.67%, time-based efficiency of 94.69%, and a 0% error rate, indicating improved efficiency compared to manual selection. UEQ results demonstrate excellent user experience across all dimensions. In conclusion, the proposed prototype effectively supports a more efficient, objective, and user-centered selection process.